Edukasi Manual Handling sebagai Preventif Musculoskeletal Disorders (MSDs) pada Pekerja Pabrik Kertas 101 Losari, Malang - Najah Fadiya Humaira; Nabila Randy Dhiyanisa; Agashi Al’Ainaa Almardyah; Diva Amanda Oliviyan; Cindy Dwi Fitria; Dwiyanti, Reni; Bayu Prastowo; Sucik Istiyaningsih; Agustina, Diana (Universitas Methodist Indonesia, 2025)
Musculoskeletal Disorder (MSDs) is one of the health problems that commonly occurs in factory workers due to repetitive physical activity with heavy loads and unergonomic conditions, with improper manual handling techniques. Manual handling is included in the ergonomics aspect in the context of physical work such as lifting, placing, pushing, and pulling heavy loads. This Community Service aims to provide manual handling education in an effort to prevent MSDs in workers at 101 Losari Paper Factory, Malang, East Java. The method used in this activity is Service Learning (SL) through action research methods in the form of lectures and demonstrations. Evaluation of workers' knowledge level was given a pre-test and a post-test. The increase in knowledge has an average shown from 11.25% to 95%. In addition, participants were able to demonstrate manual handling techniques correctly, which can be seen from the initial achievement of 25% to 83.33%. Thus, the education provided in this activity is able to increase knowledge of the application of manual handling for preventive efforts of MSDs conditions in paper factory workers.